Rozliczać? Tak, ale… - Krzyżewski, Seweryn (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
To answer the following question, one has to give some general reasons for the compensation. On the other hand, one has to examine them on the basis of some relevant variables modifying their use. Jacek Filek’s axiological theory of “demanding by values (a given response)” rooted in thinking of Roman Ingarden, Max Scheler and Nicolai Hartmann contains the best suggestion of such reasons. It has to be referred to important moments such as: who?, whom?, for what?, when?, how long?, etc. It is necessary to avoid a change of this concept into revenge.